Umbilical Cord Hematoma: A Case Report and Review of the Literature - Gennaro Scutiero; Bernardi Giulia; Piergiorgio Iannone; Luigi Nappi; Danila Morano; Pantaleo Greco (Obstetrics and Gynecology International)
Objectives. To deepen the knowledge in obstetrics on a very rare pregnancy complication: umbilical cord hematoma. Methods. A review of the case reports described in the last ten years in the literature was conducted in order to evaluate epidemiology, predisposing factors, potential outcomes, prenatal diagnosis, and clinical management. Results. Spontaneous umbilical cord hematoma is a rare complication of pregnancy which represents a serious cause of fetal morbidity and mortality. There are many risk factors such as morphologic anomalies, infections, vessel wall abnormalities, iatrogenic causes, and traction or torsion of the cord, but the exact etiology is still unknown. Conclusions. Due to the rarity of this condition, every new case of umbilical cord hematoma should be reported in order to improve the knowledge of predisposing factors, prenatal diagnosis, and clinical management.